The new reading of the invasion of Banu Qurayza, a critical investigation study (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and the best prayer and peace be upon our master Muhammad and all his family and companions. After: this research is divided into an introduction, two chapters and a conclusion:In the introduction, the researchers have explained the necessity of a new reading of some of the facts that were mentioned in the biography of the blessed Prophet, and the reason for our choice of the topic, as we explained the research plan.As for the first topic, the battle of Bani Qurayzah is mentioned as it is narrated in the novels and biography books and the reasons for the invasion and siege. Besides it is divided into two demands, the first requirement in which the battle of Bani Qurayzah is explained as it was mentioned in the narrations, the second requirement clarified the reasons for the invasion and siege of Bani Qurayza, and the second topic explained the investigation. In the incidents that came on the invasion, the first demand clarified the incident of distortion, betrayal and arbitration, the second demand clarified the incident of the execution of slaughter, the number of dead and the marriage of Rehana.  Finally there is a conclusion which consists    of the main points reached at.